A Study Of Lipid Profile In Hypertensive Patients - Shah, Siddharth; Shah, Yash; Upadhyay, Puneet; Darda, Shubham (Journal of Neonatal Surgery, 2025)
In terms of public health, hypertension ranks among the top causes of death and disability worldwide. Untreated hypertensive has a higher prevalence of dyslipidaemia than normotensives do, and lipid levels rise as blood pressure does. This study was directed towards the study of various lipid profile variables in hypertensive patients as well as it compared the lipid levels in IHD and stroke patients. Aims & Objectives: To study the lipid profile in patients of hypertension, to evaluate the abnormality of lipid profile (TC, TG, HDL-c, LDL-c, VLDL-C, TC/HDLc, LDL-c/HDL-c) in hypertensive patients and to compare the lipid levels in stroke and Ischemic Heart Disease hypertensive patients. Methodology: This study employed a cross-sectional design. Patients from the OPD as well as those admitted to the ward and intensive care unit of the General Medicine Department at Dhirai Hospital, Sumandeep Vidyapeeth, participated in this study. Out of the 100 individuals who were enrolled in the study, 50 patients with hypertension (both previously diagnosed and newly discovered cases) were chosen to participate in the research. The control population consisted of 50 patients without hypertension or its complications. Results: In our study, the minimum age of the patient was 24 years and maximum age is 86 years, the mean age was 53.67 years. Most hypertension patients in the study were between the ages of 51-60 years. In our study, 39 patients had hyperlipidaemia; all the parameters in lipid profile were raised in hypertensive population when compared it with healthy controls (normotensives);TC and LDL (P=0.0444) was raised in hypertensive patients having Stroke; the TC/HDL-c levels were raised in males as compared to females; all the parameters in lipid profile were raised in hypertensive population with IHD then with non-IHD patients; among hypertensive patients who consume alcohol, it was observed that TC, TGL and VLDL-c were raised while HDL-c were reduced in the same group. Conclusion: Our study indicates that the lipid profile of hypertension patients differs significantly from that of non-hypertensive individuals.